Empowerment-Themed Advertising Effects: Activation of Empowerment and Objectification Schemas in Women Age 18-35. Issue 3 (4th May 2023) - Couture Bue, Amelia C.; Dal Cin, Sonya; Harrison, Kristen
ABSTRACT: Advertisements that ostensibly serve to empower women have become popular in recent years, but recent research calls into question the psychological effectiveness of these advertisements. While seemingly progressive, empowerment-themed advertisements (ETAs) often pair empowerment-themed narratives with objectifying visuals despite the established harmful effects of objectification in media. Though empowerment and objectification intuitively seem incompatible, this relationship has not been empirically tested. The current study used experimental design to examine the relationship between empowerment and objectification schemas following exposure to ETAs. U.S. women age 18–35 ( N = 273) were randomly assigned to view advertisements from one of five conditions displaying combinations of high/low empowerment and objectification themes. They then completed a lexical decision task (LDT) to measure schema activation. While ETAs were perceived as significantly more empowering than other advertisement types in the manipulation check, no advertising condition exhibited greater activation of empowerment schemas than the control group as measured by the LDT, suggesting that ETAs were largely ineffective at activating empowerment schemas. Contrary to initial expectations, there was no evidence that objectification content suppressed priming of empowerment schemas, though interpretation of the objectification schema findings is complicated by the likely impact of cognitive load on LDT response times.